Social Impact Bonds in São Paulo’s state public school system: New modality of public-private partnership in Brazil - Cássio, Fernando L.; Goulart, Débora Cristina; Ximenes, Salomão Barros (Education Policy Analysis Archives, 2018)
This article analyzes the development of a new modality of public-private partnership in Brazilian education, the so-called Social Impact Bond (SIB), known in Brazil as “Contrato de Impacto Social”, whose pilot project, sponsored by the Inter-American Development Bank (IDB), is in its initial stage of implementation in the State of São Paulo. Unlike traditional philanthropy, which legitimizes itself in the alleged non-profit nature of its actions, SIB assumes the possibility of obtaining return rates with “social investments,” leading to the creation of a new ecosystem of social finances, which, into this context of privatization of education, incorporates agents interested in capitalizing on the provision of public services to vulnerable populations, in this case, to secondary students from public schools in the State of São Paulo. This kind of contract, or bond—paid by means of “delivery” of results—raises a series of ethical, legal, and political-pedagogical issues related to the accomplishment of “social experiments” with students in a vulnerable condition. From the analysis of internal documents of the Department of Education in the State of São Paulo, in comparison with documentary sources from public schools, we conclude that, from the very beginning of its implementation, the SIB of São Paulo education not only breaks with standards of scientific ethics, but also violates the principle of democratic school management included in the Brazilian constitution.